DEVELOPMENT OF COLLABORATIVE LEARNING MODELS TO IMPROVE STUDENT'S WRITING SKILLS CLASS V SD NEGERI 065011 SUB-DISTRICT MEDAN CITY - Butarbutar, Norita; Sutikno, Sutikno; Kartolo, Rahmat (Research Collaboration Community (Rescollacom), 2022)
The low interest and talent of fifth grade students at SD Negeri 065011, Medan Selayang Subdistrict, Medan City, for the 2021-2022 academic year in writing activities is caused by the absence of creativity made by educators in teaching students. For this reason, it is necessary to develop an innovative learning model that can make students more active in the process of learning to write. The learning model to be developed in this research is a collaborative learning model. The collaborative learning model is one of the